2016
DOI: 10.1021/jacs.6b10278
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Approach to Biaryls from Phenols and Aryl Sulfoxides by Temporarily Sulfur-Tethered Regioselective C–H/C–H Coupling

Abstract: We have developed metal-free regiocontrolled dehydrogenative C-H/C-H cross-coupling of aryl sulfoxides with phenols by means of trifluoroacetic anhydride. Because the reaction would proceed through an interrupted Pummerer reaction followed by sulfonium-tethered [3,3]-sigmatropic rearrangement, the C-H/C-H coupling takes place exclusively between the ortho positions of both substrates. Various functional groups including carbonyl, halo, siloxy, and even boryl moieties are compatible. The biaryl products natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(84 citation statements)
references
References 61 publications
0
84
0
Order By: Relevance
“…Based upon our previous and present experimental observations, we propose that an interrupted Pummerer reaction to form I or II , via addition of oxygen of phenols 2 (refs 42, 43, 46) or S E 2′ addition of the silanes 5 (refs 34, 35, 45) and 7 (refs 36, 37, 38) to the sulfur of activated benzothiophene S -oxide III , precedes a charge accelerated [3,3]-sigmatropic rearrangement, resulting in complete regioselective C–C bond formation at the expense of a C–H bond (Fig. 2).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Based upon our previous and present experimental observations, we propose that an interrupted Pummerer reaction to form I or II , via addition of oxygen of phenols 2 (refs 42, 43, 46) or S E 2′ addition of the silanes 5 (refs 34, 35, 45) and 7 (refs 36, 37, 38) to the sulfur of activated benzothiophene S -oxide III , precedes a charge accelerated [3,3]-sigmatropic rearrangement, resulting in complete regioselective C–C bond formation at the expense of a C–H bond (Fig. 2).…”
Section: Resultsmentioning
confidence: 58%
“…Recently, we34353637383940 and others41424344454647484950515253545556 reported the metal-free, sulfoxide directed57 C–H functionalization of a variety of molecular scaffolds, which was enabled by an interrupted Pummerer reaction28. Spurred on by these recent achievements, we considered the use of benzothiophene S -oxides 1 for the synthesis of important C3-functionalized benzothiophenes, as the corresponding sulfonium salts I and II , formed after reaction with the coupling partners, lack aromaticity about the five-membered ring and should therefore undergo facile C–C bond formation via [3,3]-sigmatropic rearrangement58, thus delivering unexplored reactivity not accessible in benzothiophenes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods mainly include three kinds of strategies: (a) rearrangement of aromatic O–X bonds151617181920; (b) directing group-assisted ortho C–H hydroxylation of arenes21222324252627; and (c) ortho C–H functionalization of phenols2829303132. Although these results have promoted the development of the phenol chemistry, the more efficient, economical and biocompatible methods are still in demand.…”
mentioning
confidence: 99%
“…A well-chosen electrophilic sulfenylation reagent would facilitate the N -sulfenylation of the X–N moiety and lead to the formation of an N–S bond to produce intermediate B ; (ii) rearrangement. Pivotal progress was made by Maulide4041, Procter3242, Yorimitsu31 and Peng43 who pioneered the directed, metal-free, redox-neutral and ortho -functionalization. These inspiring work suggested that when the substrate captured a suitable partner, the resulting intermediate may undergo a sigmatropic rearrangement and rearomatization to product D , leading to the formation of a C–X bond with concurrent O–X bond cleavage.…”
mentioning
confidence: 99%